Genome-wide analysis of the WSD family in sunflower and functional identification of HaWSD9 involvement in wax ester biosynthesis and osmotic stress - Zhang, Cheng; Yang, Jiabao; Meng, Wanqiu; Zeng, Linglu; Sun, Li (Frontiers in Plant Science, 2022)
The wax esters are important cuticular wax composition that cover the outer surface of plant organs and play a critical role in protection and energy metabolism. Wax ester synthesis in plant is catalyzed by a bifunctional wax ester synthase/acyl-CoA: diacylglycerol acyltransferase (WSD). Sunflower (Helianthus annuus L.) is an important oil crop in the world; however, little is known about WSD in sunflower. In this study, we identified and performed a functional analysis of twelve HaWSD genes from sunflower genome. Tissue-specific expression revealed that 12 HaWSD genes were differentially expressed in various organs and tissues of sunflower, except seeds. HaWSD genes were highly induced by salinity, drought, cold, and abscisic acid (ABA) in sunflower. To ascertain their function, HaWSD9, with highly expressed levels in stems and leaves, was cloned and expressed in a yeast mutant defective in triacylglycerol (TAG) biosynthesis. HaWSD9 complemented the phenotype by producing wax ester but not TAG in vivo, indicating that it functions as a wax ester synthase. Subcellular localization analysis indicated that HaWSD9 was located in the endoplasmic reticulum (ER). Heterologous introduction of HaWSD9 into Arabidopsis wsd1 mutant exhibited increased epicuticular wax crystals and cuticular wax contents on the stems. As compared with the wsd1 mutant, HaWSD9 overexpressing transgenic Arabidopsis showed less cuticle permeability, chlorophyll leaching and water loss rate. Further analysis showed that the HaWSD9 transgenics enhanced tolerance to ABA, mannitol, drought and salinity, and maintained higher leaf relative water content (RWC) than the wsd1 mutant under drought stress, suggesting that HaWSD9 play an important physiological role in stress response as well as wax synthase. These results contribute to understanding the function of HaWSD genes in wax ester synthesis and stress tolerance in sunflower.